In the Course of Performance: Studies in the World of Musical Improvisation - Nettl, Bruno; Russell, Melinda (Chicago University of Chicago Press, 1998)
In the Course of Performance is the first book in decades to illustrate and explain the practices and processes of musical improvisation. Improvisation, by its very nature, seems to resist interpretation or elucidation. This difficulty may account for the very few attempts scholars have made to provide a general guide to this elusive subject. With contributions by seventeen scholars and improvisers, In the Course of Performance offers a history of research on improvisation and an overview of the different approaches to the topic that can be used, ranging from cognitive study to detailed musical analysis. Such diverse genres as Italian lyrical singing, modal jazz, Indian classical music, Javanese gamelan, and African-American girls' singing games are examined. The most comprehensive guide to the understanding of musical improvisation available, In the Course of Performance will be indispensable to anyone attracted to this fascinating art.Contributors are Stephen Blum, Sau Y. Chan, Jody Cormack, Valerie Woodring Goertzen, Lawrence Gushee, Eve Harwood, Tullia Magrini, Peter Manuel, Ingrid Monson, Bruno Nettl, Jeff Pressing, Ali Jihad Racy, Ronald Riddle, Stephen Slawek, Chris Smith, R. Anderson Sutton, and T. Viswanathan.
Keywords: Improvisation